1998
DOI: 10.1111/j.1440-1746.1998.tb00654.x
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORT: An inherited APC mutation in the first reported Australian case of Turcot's syndrome

Abstract: The objective of this study was to determine the inherited gene mutation responsible for the first reported Australian case of Turcot's syndrome. DNA was extracted from the archival tissue blocks obtained at the time of the patient's original surgery and from fresh blood samples obtained from selected family members. These were analysed for mutations of the familial adenomatous polyposis gene (APC). Analysis of DNA from the archival blocks and from each of the affected family members revealed an inherited 5 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Hamilton et al 12 first reported an APC patient whose medulloblastoma contained a homozygous protein truncating mutation. The increased risk of central nervous system (CNS) tumours in APC patients, the high expression of APC in developing and adult rodent CNS,39-42 and scattered mutational reports12 43 suggest that a loss of APC function can be a causative factor in the development of neuroepithelial tumours. This also provides a rationale for assaying sporadic neuroepithelial tumours for APC mutations.…”
mentioning
confidence: 99%
“…Hamilton et al 12 first reported an APC patient whose medulloblastoma contained a homozygous protein truncating mutation. The increased risk of central nervous system (CNS) tumours in APC patients, the high expression of APC in developing and adult rodent CNS,39-42 and scattered mutational reports12 43 suggest that a loss of APC function can be a causative factor in the development of neuroepithelial tumours. This also provides a rationale for assaying sporadic neuroepithelial tumours for APC mutations.…”
mentioning
confidence: 99%